Impact of aminoglycosides on survival rate and renal outcomes in patients with urosepsis: a multicenter retrospective study - David Rozenblat; Arnaud Serret-Larmande; Alexis Maillard; Romain Arrestier; Sarah Benghanem; Julien Charpentier; Michael Darmon; Vincent Das; François Dépret; Jean Luc Donay; Hervé Jacquier; Hélène Poupet; et al. (Annals of Intensive Care)
Abstract Background Combination therapy with a beta-lactam and an aminoglycoside is currently recommended for the empirical treatment of urosepsis. Nephrotoxicity is the most common adverse effect of aminoglycosides and acute kidney injury (AKI) has a significant prognostic impact in septic shock. This study aimed to evaluate the impact of empirical antibiotic therapy with or without an aminoglycoside on survival and renal outcomes in patients admitted to the intensive care unit (ICU) with urosepsis. Methods This multicenter, retrospective, comparative study included all adults admitted to the ICU for urinary sepsis or septic shock between January 2015 and May 2022 in four ICUs of three university hospitals within the Assistance Publique—Hôpitaux de Paris (APHP). The primary outcome was mortality on day 30 after ICU admission. Secondary endpoints included the lack of renal recovery, the need for new renal replacement therapy (RRT), the Major Adverse Kidney Events at day 30 (MAKE 30) and ICU length of stay. Confounding by indication was taken into account using propensity score weighting. Results A total of 580 patients were included, median age was 69 years (interquartile: 58–77) and 53.6% were male. Overall, 335 patients (57.8%) were in septic shock and 448 (79.2%) had AKI on admission. A total of 579 patients (99.8%) received a beta-lactam as empirical therapy (with (n = 444) or without (n = 136) aminoglycosides). The overall 30-day mortality rate was 10.5% (61/580). After propensity score weighting, the mortality rate in patients receiving aminoglycosides was 7.7% (7/91) compared to 12.1% (11/91) in those not receiving aminoglycosides (adjusted hazard ratio (aHR) = 0.65 [0.35; 1.23], p = 0.19). No significant differences were found in the lack of renal recovery at day 30 (aHR = 0.88 [0.49; 1.58], p = 0.67), the need for new RRT within 30 days (aHR = 1.01 [0.54; 1.88], p = 0.97), MAKE 30 (aHR = 0.94 [0.60; 1.50], p = 0.81), and ICU length of stay among survivors (aHR = 1.07 [0.87; 1.31], p = 0.53). Conclusions Including aminoglycosides in the empirical antibiotic therapy did not significantly improve 30-day survival in patients admitted to the ICU for urosepsis. However, the use of aminoglycosides was not associated with worse renal outcomes.